Effect of Development on the Translation of Messenger RNA in Artemia salina Embryos - Sierra, José M. (1974)
Cell-free preparations from encapsulated Artemia salina embryos readily translate poly(U), but there is no endogenous protein synthesis or translation of added natural mRNA until development resumes upon incubation in saline. High-salt-washed 80S ribosomes and highspeed supernatant (cytosol) were prepared from undeveloped eggs and from eggs allowed to develop to a stage prior to hatching. Endogenous protein synthesis occurs only with ribosomes from developed embryos, whether with undeveloped or developed cytosol. This is mainly elongation of preformed polypeptide chains, for it is largely resistant to edeine, an inhibitor of chain initiation. Edeinesensitive translation of added natural mRNA occurs with both developed and undeveloped ribosomes but requires developed cytosol. Translation of brome mosaic virus RNA is not much, if at all, further stimulated by high-saltwash of developed ribosomes, but that of globin mRNA is markedly enhanced. Levels of the chain initiation factor EIF-1 are the same before and after development. These results are consistent with the view that resumption of developemtn is triggered by transcription, with ensuing translation of the resulting messengers to yield, among other proteins, mRNA-recognizing initiation factors of the IF-3 type which are partly free in the cytosol and partly ribosome-bound. The data also suggest that different factors may be involved in the translation of brome mosaic virus RNA and globin mRNA by this system.